Implementation of a MIMO SAR Imaging Mode for NASAs Next Generation Airborne L-Band SAR - Krieger, Gerhard; et al. (European Conference on Synthetic Aperture Radar (EUSAR), 2018)
Radar systems with multiple transmit and multiple receive channels (MIMO) are capable of advanced imaging modes that can benefit the next generation of Earth science and planetary science Synthetic Aperture Radar (SAR) missions. Apart from an increased flexibility, MIMO SAR enables simultaneous full-polarized acquisitions without any reduction of the swath width or resolution. By making use of an innovative orthogonal-waveform beamforming technique, sufficient suppression of cross-correlation interference from orthogonal signals can be achieved. For verification of this MIMO SAR imaging mode, the airborne radar sensor DBSAR-2 operated by NASA will serve as a test bed.
Keywords: multiple-Input multiple-output; MIMO; digital beamforming; DBF; synthetic aperture Radar; SAR; orthogonal waveform; polarimetry